Air-water interaction and characteristics in breaking bores. (November 2019) - Leng, Xinqian; Chanson, Hubert
Highlights: In a two-phase breaking bore roller, air entrainment takes place in the form of air entrapment at the roller toe, air-water exchange across the roller 'free-surface', spray and splashing with dynamic water drop ejection and reattachment, roll up and roll down of water 'tongues' engulfing air pockets. All experimental measurements indicated a relatively short and thin air-water flow region. The number of air bubbles within the roller was limited, chord lengths spanned over several orders of magnitude, with increasing chord size with increasing vertical elevation within the roller. Large proportion of clustered bubbles were observed and the clustering characteristics were similar to those in stationary hydraulic jumps. Results could serve as a validation frame for computational fluid dynamics (CFD) modelling, as the modelling of air-water interactions in breaking rollers of hydraulic jumps and tidal bores remain a huge challenge for numerical modeller. Abstract: A tidal bore is an unsteady rapidly-varied open channel flow characterised by a rise in water surface elevation in estuarine zones, under spring tidal conditions. After formation, the bore is traditionally analysed as a hydraulic jump in translation and its leading edge is characterised by a breaking roller for Froude number Fr1 > 1.3–1.5. The roller is a key flow feature characterised by intense turbulence and air bubble entrainment. Detailed unsteady air-water flow measurements were conducted in a breaking bore propagating in a large-size channel, using an array of three dual-tip phase detection probes and photographic camera. The data showed a relatively steep roller, with a short and dynamic bubbly flow region. Air entrainment took place in the form of air entrapment at the roller toe, air-water exchange across the roller 'free-surface', spray and splashing with dynamic water drop ejection and re-attachment, roll up and roll down of water 'tongues' engulfing air pockets. The roller free-surface profile and characteristics were comparable to observations in stationary hydraulic jumps and steady breaker, for similar flow conditions. Within the roller, the amount of entrained air was quantitatively small for Froude number Fr1 = 2.2. The number of air bubbles was limited, with between 5 and 20 bubbles per phase-detection probe sensor detected at each vertical elevation. The entrained air bubble chord lengths spanned over several orders of magnitude, with a large proportion of clustered bubbles. Overall, the study highlighted the three-dimensional nature of the air-water roller motion and strong evidence of the in-homogeneity of the turbulent air-water mixture.